METAL CONTAMINATION OF THREE COMMERCIALLY FISH SPECIES COLLECTED FROM ACEH (INDONESIA) AND PENANG (MALAYSIA) - Sofia, Sofia (Universitas Syiah Kuala, 2009)
Concentrations of lead (Pb), cadmium (Cd), and copper (Cu) were determined in muscle and liver tissue in the three commercially fish species, the Indian mackerel (Rastrellinger kanagurta), the tuna (Euthynnus affinis), and the tripletail (Lobotes surinamensis) collected from Aceh (Indonesia) and Penang (Malaysia). In this study, metal concentrations were found highest in the liver tissue compared to the muscle for all fish species (P0.05). Concentrations ofmetals in the liver were in the range of 0.05 to 0.4 0g/g dry wt for Pb, from 0.13 to 0.67 0g/g dry wt. for Cd, and 1.17 to 3.54 0g/g dry wt. for Cu. While in the muscle, Pb content were in the range of 0.02 to 0.14 0g/g dry wt.; Cd at below 0.12 0g/g dry wt.; and Cu at below 0.54 0g/g dry wt. On the average, among locations, Pb, Cd, and Cu contamination were found significantly higher (P0.05) in samples collected from Aceh (Indonesia). However, levels of metals in the fish studied were not exceeded the guideline values for food as recommended by Ministry of Agriculture, Fisheries, and Food, UK and the Ministry of Health Malaysia.